Kinetics of dehydration of potato and development of baked product based on dehydrated potato (Journal of the Bangladesh Agricultural University, 2013)
The aims of this study were to determine the kinetics of dehydration of high yielding potato variety (Diamont), to investigate the various process parameters influencing mechanical drying of potatoes and to develop baked product from the dehydrated potato. From the developed equation it was found that the diffusion co-efficient increased with the increase in temperature. The exponential relationship between diffusion co-efficient (De) versus inverse absolute temperature (Tabs-1), activation energy (Ea) for diffusion of water HYV potato was found to be 7.98 Kcal/gm-mole. The influence of loading density as well as thickness of the product on drying rate were determined and the power law equations which described the relationship between drying rate constant and thickness gave an n-value of 0.4586 for HYV of potato. Organoleptic taste tests demonstrated that among biscuits made of various proportion of potato flour and wheat flour, the results of test panel showed that biscuit made of equal proportion (1:1) of potato flour and wheat flour secured the highest score (8.0). All the other samples of each type of product were also accepted by the panelists either as like moderately or like slightly.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14923 J. Bangladesh Agril. Univ. 10(2): 303-312, 2012